Conservative Management of Cesarean Scar Ectopic Pregnancy with Fetal Heart Activity and a Very High β-hCG - Rodney McLaren; Sandra McCalla; Mohamad Irani (Case Reports in Obstetrics and Gynecology)
Cesarean scar ectopic pregnancy (CSP) is a rare type of ectopic pregnancy that is growing in incidence. The diagnosis of most CSP occurs when patients present in unstable conditions requiring surgical management and leading sometimes to hysterectomy. It has been shown that medical management is a safe option for early diagnosed hemodynamically stable CSP. However, no cases of CSP with β-hCG higher than 62,000 IU/L, conservatively treated, have been reported. We report the case of a 29-year-old patient who presented for her first prenatal visit at 13-week gestation and was diagnosed with CSP with present fetal heart tones and a quantitative β-hCG of 144,337 IU/L. She was treated with bilateral uterine artery embolization and systemic methotrexate. Her β-hCG significantly decreased and became undetectable within 10 weeks. We propose that patients with CSP with very high β-hCG and fetal heart activity can be offered conservative or fertility preserving management.